Functional Analysis of Wheat NAC Transcription Factor, TaNAC069, in Regulating Resistance of Wheat to Leaf Rust Fungus - Zhang, Yanjun; Geng, Huaimin; Cui, Zhongchi; Wang, Haiyan; Liu, Daqun (Frontiers in Plant Science, 2021)
NAC transcription factors are one of the largest transcription factor families, having functions in a variety of stress responses. Few NACs have been reported for interactions between wheat and the wheat rust fungus Puccinia triticina (Pt). In this study, based on analysis of RNA-seq data from wheat line TcLr19 inoculated by Pt, the NAC transcription factor TaNAC069 was cloned from wheat, and its transcriptional activity and homologous dimer formation was verified. Quantitative real-time PCR (qPCR) analysis showed that expression of TaNAC069 was induced by Pt and associated signaling molecules. To further characterize the function of the TaNAC069 gene in wheat resistance to Pt, virus-induced gene silencing (VIGS) was utilized, and revealed that Pt resitance in TaNAC069-silenced plants was significantly reduced. Potential interaction targets of TaNAC069 from wheat and Pt were screened and identified by yeast two-hybrid technology. Eukaryotic elongation factor eEF1A, CBSX3 protein, cold acclimation protein WCOR410c were screened by yeast one-hybrid technology. Results indicate that the TaNAC069 gene plays a positive regulatory role in wheat resistance to Pt, laying a good foundation to analyze the molecular mechanisms of TaNAC069 and its functional role in wheat resistance to Pt.